Proceso de Baja de Bienes de la Universidad Técnica de Babahoyo - Rodríguez Gil, Jairon Alberto (2017)
The Technical University of Babahoyo is an identity that provides its work in higher education to train professionals in the different branches of their knowledge, with ethical and moral values ​​to contribute to the social and economic transformation of the country. The institution counts on different departments to execute diverse activities, they are subject to process of administration and control that entail to parameters and make that each one of its functions is carried out with efficiency and efficiency